Delayed Antiviral Immune Responses in Severe Acute Respiratory Syndrome Coronavirus Infected Pregnant Mice - Zhu, Guohua; Du, Shujuan; Wang, Yuyan; Huang, Xixi; Hu, Gaowei; Lu, Xin; Li, Dajin; Zhu, Yizhun; Qu, Di; Cai, Qiliang; Liu, Lu; Du, Meirong (Frontiers in Microbiology, 2022)
Sex differences in immune responses had been reported to correlate with different symptoms and mortality in the disease course of coronavirus disease 2019 (COVID-19). However, whether severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection interferes with females' fertility and causes different symptoms among pregnant and non-pregnant females remains unknown. Here we examined the differences in viral loads, SARS-CoV-2-specific antibody titers, proinflammatory cytokines, and levels of T cell activation after SARS-CoV-2 sub-lethal infection between pregnant and non-pregnant human Angiotensin-Converting Enzyme II (ACE2) transgenic mouse models. Both mice showed elevated levels of viral loads in the lung at 4 days post-infection (dpi). However, viral loads in the pregnant group remained elevated at 7 dpi while decreased in the non-pregnant group. Consistent with viral loads, increased production of proinflammatory cytokines were detected from the pregnant group, and the IgM or SARS-CoV-2-specific IgG antibody in serum of pregnant mice featured delayed elevation compared with non-pregnant mice. Moreover, by accessing kinetics of activation marker expression of peripheral T cells after infection, a lower level of CD8+ T cell activation was observed in pregnant mice, further demonstrating the difference of immune-response between pregnant and non-pregnant mice. Although vertical transmission did not occur as SARS-CoV-2 RNA was absent in the uterus and fetus from the infected pregnant mice, a lower pregnancy rate was observed when the mice were infected before embryo implantation after mating, indicating that the mice were infected after mating, SARS-CoV-2 infection may interfere with mice’s fertility at a specific time window. In summary, pregnant mice bear a weaker ability to eliminate the SARS-CoV-2 virus than non-pregnant mice, which was correlated with lower levels of antibody production and T cell activation.